Гербарій Національного ботанічного саду ім. М.М. Гришка НАН України - Melnik, V.I.; Didenko, S.Ya.; Bagatska, T.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The history of Herbarium of M.M. Gryshko National Botanical Gardens of National Academy of Sciences of Ukraine that was founded by S.S. Kharkevich has been done. The work of that scientific department was analyzed during 60 years. The list of organizations that were given its herbarium collection material and names of the most active collectors has been done. There are submitting results of original studies of Native Flora Department research workers for consideration. To put forward the suggestion: the Herbarium will be named S.S. Kharkevich.